Hubungan Gambaran Foto Toraks dengan Derajat Keparahan Pasien COVID-19 di RSPAL dr. Ramelan - MILLENIAWATI PUTRI NOVITANIA; RIKE ANDY WIJAYA; LILIAWANTI; DIAH PURWANINGSARI (HANG TUAH MEDICAL JOURNAL, 2022)
Background : The COVID-19 pandemic induced a challenge of the importance of diagnostic evaluation. This includes understanding signs and symptoms in diagnosing the probability of infection. The amount of clinical symptoms from the confirmed COVID-19 patient is the same as the other respiratory diseases, which makes it hard to diagnose at the beginning. The gold standard examination of COVID-19 is RT-PCR test and additional examination that usually done is radiology examination. The most used radiology examination is chest X-ray to identify any anomaly in patient's lungs and to evaluate the disease progress. The purpose of this research is to understand the existence of correlation between chest X-ray imaging and severity degree of COVID-19 patients that are treated in RSPAL dr. Ramelan Surabaya from November 2020-January 2021. Methods : The type of research is analytical observational study with case control design using 44 samples obtained from medical history of inpatients and outpatients that are confirmed positive of COVID-19 treated in RSPAL dr. Ramelan Surabaya in span of November 2020-January 2021. Bivariate analysis was performed using Spearman's test Results : From the result of bivariate analysis using Spearman's test appears significance score (p) = 0.0001 which <0.05 that shows the significant existence of connection between chest X-ray image and severity degree of COVID-19 patients. It is also found that the coefficient correlation score (r ) = 0.985 shows a positive correlation with strong correlation power. Conclusion : There is a connection between chest X-ray images and severity degree of COVID-19 patients. The more severe the clinical symptoms of a patient, the worse that patient's chest X-ray result will be. Keywords : COVID-19, Chest x-ray imaging, Severity degree.